Improving the environmental performanof fish-farming houses: A comparative passive design study in South Korea - Lee, Kyu In; Cho, Yoon Boum; Yi, Hwang (Journal of Green Building, 2020)
Aquaculture in South Korea largely involves crudely-built plastic fishery houses that consume excessive electricity and produce carbon emissions. This study explores a potential method to make Korean aquaculture more sustainable by suggesting design alternatives that can save energy and costs. To this end, the authors compare the energy use and indoor environments of three different designs through field mockups. The three designs include (i) a triple-layered plastic screen house (Design 1), (ii) an insulated vault house (Design 2), and (iii) a passive-house design (Design 3), in addition to (iv) a single-layered plastic house (baseline). Our findings indicate that, compared to the baseline, operational electricity was reduced to 57.81% in Design 1, 53.92 % in Design 2, and 40.59% in Design 3. Moreover, Designs 2 and 3 were able to mitigate indoor temperature fluctuations in winter. Design 1 showed a relatively unstable temperature distribution during the night but offered better farming conditions than the baseline. Humidity often rose to 100% but did not affect the maintenance of a desirable fish and workplace environment. Even a high concentration of carbon dioxide of up to 3,000 ppm in Designs 1 and 2 was not expected to harm farmers’ health. Cost analyses revealed that construction expenses increased to 20.9% in Design 1, 135.8% in Design 2, and 73.9% in Design 3 due to large quantities of materials and labor. Considering trade-offs with energy saving, the payback period is 7.2 years for Design 1, 35.5 years for Design 2, and 17.9 years for Design 3. Given that the lifetime expectancy of Designs 1 and 3 is over two years, the study’s results confirm that Designs 1 and 3 have a comparative advantage in producing sustainable fish-farming houses.
Keywords: Carbon emissions; Comparative advantage; Design alternatives; Indoor environment; Indoor temperature; Payback periods; Potential methods; Workplace environments; Aquaculture; Building performance; Fish-farming house; Passive house; Sustainability